2005
DOI: 10.2460/javma.2005.227.1646
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal problems associated with lameness and poor performance among horses used for barrel racing: 118 cases (2000–2003)

Abstract: Results suggest that in horses used for barrel racing that are examined because of lameness or poor performance, the forelimbs are more likely to be affected than the hind limbs, with forelimb foot pain and osteoarthritis of the distal tarsal joints being the most common underlying abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 9 publications
8
41
2
Order By: Relevance
“…These movements associated with the breed standard can lead to certain injuries. Contrary to previously reported (DABAREINER et al, 2005;MENARIM et al, 2012), this study reported higher incidence of pelvic tendons injuries and a tendency towards greater frequency of femoral-tibial-patellar and tarsus injuries in western sports animals than in jumping animals. There is a tendency to higher incidence of femoral-tibial-patellar injuries when compared to working animals (CONTINO et al, 2012;Smith (1993) apud TIPTON et al, 2013.…”
Section: -------Dressage--------------racing------------polo Pony----contrasting
confidence: 99%
See 4 more Smart Citations
“…These movements associated with the breed standard can lead to certain injuries. Contrary to previously reported (DABAREINER et al, 2005;MENARIM et al, 2012), this study reported higher incidence of pelvic tendons injuries and a tendency towards greater frequency of femoral-tibial-patellar and tarsus injuries in western sports animals than in jumping animals. There is a tendency to higher incidence of femoral-tibial-patellar injuries when compared to working animals (CONTINO et al, 2012;Smith (1993) apud TIPTON et al, 2013.…”
Section: -------Dressage--------------racing------------polo Pony----contrasting
confidence: 99%
“…Our results corroborate previous studies conducted in other countries (CHENEY et al, 1973;MEERSHOEK et al, 2001;DYSON, 2002;DABAREINER et al, 2005;MURRAY et al, 2006;DYSON, 2007;COGGER et al, 2008;SCOTT, 2008;MURRAY et al, 2010;MENARIM et al, 2012) and it can be useful in identifying risk factors to these injuries, to propose changes in management, handling and training in order to prevent losses, suffering of animals and financial losses.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations